ANALISIS PERBANDINGAN RETURN ON ASSET (ROA), DEBT TO ASSET RATIO (DAR) DAN CURRENT RATIO (CR) PADA PT. INDOCEMENT TUNGGAL PRAKARSA, TBK DENGAN PT. SOLUSI BANGUN INDONESIA, TBK - Lestari Munawarah; Aliah Pratiwi; Alwi Alwi (JOURNAL SAINS STUDENT RESEARCH, 2024)
This research aims to determine and analyze the comparison of Return on Assets (ROA), Debt to Asset Ratio (DAR) and Current Ratio (CR) at PT. Indocement Tunggal Prakarsa, Tbk with PT. Solusi Bangun Indonesia, Tbk. The type of research used by researchers in this research is comparative research. The research instrument used is a list of tables containing data on net profit, total assets, total debt, current assets and current debt obtained from the balance sheet and profit and loss financial statements at PT. Indocement Tunggal Prakarsa, Tbk and PT. Solusi Bangun Indonesia, Tbk from 2013-2022. The population used in this research is the financial statements of PT. Indocement Tunggal Prakarsa, Tbk since being listed on the IDX from 1989 to 2022, namely for 33 years and PT. Solusi Bangun Indonesia, Tbk has been listed on the IDX from 1977 to 2022, which is 45 years. The sample in this research is the financial report of PT. Indocement Tunggal Prakarsa, Tbk and PT. Solusi Bangun Indonesia, Tbk for 10 years, namely from 2013 to 2022. The sampling technique used in this research was purposive sampling technique. Data collection techniques in this research are documentation and literature study. The statistical analysis used in this research is the Independent Sample T test. The research results show that there are significant differences in Return On Assets, Debt to Asset Ratio (DAR) and Current Ratio (CR) at PT. Indocement Tunggal Prakarsa, Tbk and PT. Solusi Bangun Indonesia, Tbk.